Taxation and the Conservation of Resources - Ciriacy-Wantrup, S. V. (Quarterly Journal of Economics, 1944)
Taxation and the Conservation of Resources Get access The Quarterly Journal of Economics, Volume 58, Issue 2, February 1944, Pages 157–195, https://doi.org/10.2307/1883316 Published: 01 February 1944